Comparative study on lighting and ventilation of two kindergarten typologies in Selangor - Chai, Mei Yiw; Hazrina Haja Bava Mohidin (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper aims to investigate the spatial quality in kindergartens by comparing two different kindergarten typologies based on lighting and ventilation as design factors. Most kindergartens in Malaysia are converted from either a house or a shop lot that were not purposely built to suit the functions of a good learning environment. This has caused restrictions on space planning and affects the learning quality of the children. Past works have shown studies on space effectiveness in terms of safety, security and comfort level based on user perception, however, there were no research done on spatial quality of kindergartens with regards to lighting and ventilation as design factors. This research is important as it justifies and suggests the better type of building that can be converted into a kindergarten to provide better learning environment for the children from the two most popular type in Selangor ; dwelling-type and shop lot-type kindergarten. A case study method is utilized to analyze these two different types of kindergarten in Selangor by focusing on the design factors mentioned above. The findings will provide a comprehensive data that can be used as a basis for future research in the field of learning environment and as a reference in preparing kindergarten set up requirements in the future in order to achieve the best design approach in designing the effective learning environment in kindergartens.